How to achieve the most success with online recruiting: the spread of online recruiting and its impact - Zhang, Jianan (2012)
It is no news that the labour market is still highly competitive, attracting and retaining talent has now become the number one challenge facing all companies. With Internet penetrating in our daily life, organizations are taking advantage of it by adopting online recruiting methods. Recruitment processes have changed a lot since we entered into information era, recruiting efforts have evolved from traditional newspaper ads to sophisticated web sites. The whole complexion of recruiting has changed, with Internet; information that is needed can be accessed with a few clicks of a mouse. By using the Internet properly recruiters are able to fill more positions in shorter time. What’s more, unlike printed ads, job positions can now be posted, deleted and edited in seconds on their career websites or any job boards. Internet is now playing an increasingly important role in recruiting, reasons behind this trend will be discussed in this paper. Compared to traditional recruiting methods, both advantages and limitations of online recruiting will be presented in order to evaluate the efficiency of its use in organizations. Although Internet has occupied a part of our life for quite a long time, it is a relatively new area for it being used in corporate recruiting. This paper examines the impact of the spread of online recruiting for the past decades by presenting an empirical research. Following a review of literature, methodology utilised to obtain and analyse online recruiting queries will be presented. Interviews will be conducted and questionnaires will be sent out in order to gain the information concerned. After that, discussion of the major findings will be presented, and finally key points of this paper and future research directions are outlined.